Breath analysis for in vivo detection of pathogens related to ventilator-associated pneumonia in intensive care patients: a prospective pilot study. (5th January 2015) - Filipiak, Wojciech; Beer, Ronny; Sponring, Andreas; Filipiak, Anna; Ager, Clemens; Schiefecker, Alois; Lanthaler, Simon; Helbok, Raimund; Nagl, Markus; Troppmair, Jakob; Amann, Anton
Abstract: Existing methods for the early detection of infections in mechanically ventilated (MV) patients at intensive care units (ICUs) are unsatisfactory. Here we present an exploratory study assessing the feasibility of breath VOC analyses for the non-invasive detection of pathogens in the lower respiratory tract of ventilated patients. An open uncontrolled clinical pilot study was performed by enrolling 28 mechanically ventilated (MV) patients with severe intracranial disease, being at risk for the development of or already with confirmed ventilation-associated pneumonia (VAP). The recently developed sampling technique enabled the collection of breath gas with a maximized contribution of alveolar air directly from the respiratory circuit under continuous capnography control, adsorptive preconcentration and final analysis by means of gas chromatography-mass spectrometry (GC-MS). VAP was confirmed in 22/28 preselected patients (78%). The most common microorganisms were Staphylococcus aureus (5/22 VAP patients), Escherichia coli (5/22 VAP patients) and Candida spp . (5/22 VAP patients). 12/32 metabolites released by S. aureus in our previous in vitro studies were also detected in the end-tidal air of VAP patients infected with this pathogen. A similar overlap was seen in Candida albicans infections (8/29 VOCs). Moreover, the concentration profile of selected compounds correlated with the course of the infection. This prospective pilot study provides proof of the concept that the appearance and the concentration profile of pathogen-derived metabolites (elucidated from in vitro experiments) in the breath of ventilated patients during clinically confirmed VAP correlates with the presence of a particular pathogen.